METODE DEKOMPOSISI ADOMIAN UNTUK MENYELESAIKAN PERSAMAAN PANAS - Andi Tri Wardana; Yuni Yulida; Na’imah Hijriati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2015)
The differential equation is an equation in which there is a derivative of one or more independent variables. The differential equation can be divided into two groups, Ordinary differential equation and Partial differential equation. One method for solving ordinary differential equations is the Adomian Decomposition Method which is used to facilitate in the solving of ordinary nonlinear differential equations. Adomian decomposition method is a method that can also be used to determine the solution of partial differential equations, one of which can be applied to the heat equation. This study was conducted using literature study. The results of this study show that the solution of the linear heat equation is: 1100 (,) (,) (, 0) (,) (,) nttxxnnnuxtuxtuxLgxtLLuxt∞∞ - ==  == ++ ΣΣ with 10 ( ,) (, 0) (,) tuxtuxLgxt - = + and 1 (,) (,), 1,2,3, ... ntxxnuxtLLuxtn - == and the solution of nonlinear heat equation is: 11000 (,) (,) (, 0) (,) (,) ntxxntnnnnuxtuxtuxLLuxtLAxt∞∞∞ - ===== ++ ΣΣΣ with 0 (,) (, 0) uxtux = and 111 (,) (,) (,), 0,1,2, ... ntxxntnuxtLLuxtLAxtn - + = + =